The iliosacral articulation in Pseudinae (Anura: Hylidae) - Manzano, Adriana Silvina (2005)
We analyzed the iliosacral joint and iliolumbaris muscle anatomy of the species of Pseudinae, based on the two types of articulations defined by Emerson. Unusual characters should be expected in the pseudine iliosacral articulation structure, given their aquatic habits and evolutionary history. In fact, the presence of a ligamentous cap joining the ilium with the sacral diapophysis has not been described previously, and may be unique to pseudines. This particular group lacks a single pattern of iliosacral articulation for the whole subfamily, and the articulations are not strictly referable to any of the types or subtypes described by Emerson. The iliosacral articulation is interspecifically variable within Pseudinae and is intermediate between the articulations of Type IIA and IIB.